Assessing Banking and Currency Crisis Risk in Small States : An application to the Eastern Caribbean Currency Union - Pizzinelli, Carlo (IMF Working Papers; Working Paper ;, 2021)
To complement the early warning signals literature, we study the determinants of banking and currency crises for small states and currency boards. Building on the crisis dataset by Laeven and Valencia (2020), we estimate a binominal logit model to identify the determinants of crises, and as a case study, we apply our models to the Eastern Caribbean Currency Union (ECCU). Our findings largely confirm past studies' results that both external and domestic fundamentals matter in predicting crisis likelihood, but we find that small states and fixed exchange rate regimes are more sensitive to these fundamentals, compared to larger economies. Our empirical results also suggest that for currency board economies, keeping a high level of the foreign reserve cover-the 'backing ratio' defined as official foreign reserves as a share of central bank demand liabilities-is critical to reduce the likelihood of both banking and currency crises. The backing ratio is particularly important during years of global economic downturn.